Analysis of Glacial Front Dynamics in Hornsund Fjord (Svalbard) Over 30 Years Using Landsat Multispectral Imagery - Modlińska, Paulina; Kopeć, Anna; Mróz, Filip (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study investigates the long-term dynamics of glacier fronts in the Hornsund Fjord (Svalbard) over a 30-year period (1992-2023), utilizing multispectral Landsat satellite imagery in conjunction with advanced GIS-based methods. While numerous studies have examined glacial retreat using photogrammetry or field measurements, this research addresses a semi-automated approach that integrates raster segmentation and supervised classification for precise front delineation and the calculation two types of indicators of curvature of glacial front (CfD and CfE).
Keywords: glacier fronts; glacial indicators; Landsat; Svalbard; multispectral imaging